(untitled) (International Journal of Academic Research in Progressive Education and Development, 2022)
This paper is to investigate and understand perspectives held by a diverse group of people in a multicultural school setting in Malaysia. It examined the understanding of, and attitudes towards language diversity of school administrators, teachers and students in a specific school setting. The study drew on literature in the field of multi/interculturalism, and used a qualitative case study approach employing an interview approaches. The paper examined the concept of language diversity as a social phenomenon and links current understanding of the phenomenon to that of the people involved, explaining how and why they think, respond and react the way they do. A national primary school was chosen for the case study. In Malaysia, the government has embarked on an ambitious program to promote national primary schools as ‘a school of choice’ as an attempt to promote ‘unity in diversity’. School administrators, teachers, and students of this particular type of school were interviewed and the data analysed. The respondents practice Bahasa Melayu and English as the main medium of communication (lingua franca) and as a reflection on the increasing importance of this, they expect all students to take advantage and benefit from learning them both. However, the social factors and different environments are somehow conclusively determined to influence the way the language is used and learned by young children in MNS. Many Indians and some Chinese students, who came from the lower social background and speak their ‘mother-tongue’ at home, seem to experience difficulty in communication with people of the other race, especially during the classroom teaching and learning. At the end, the respondents drew attention to the way in which racial integration in MNS might be deteriorating, possibly by the use of the first language or/and the diversity of the language used in the school.